Odnowa życia zakonnego w świetle Soboru Watykańskiego II i w nauczaniu magisterium Kościoła - Piotr Jamioł (Polonia Sacra)
Discussion Document on the Church’s renewal of religious life in the light of Vatican II and the teaching of the Magisterium of the Church.